Changes in the Bacterial Community Associated With Experimental Symbiont Loss in the Mucus Layer of Cassiopea xamachana Jellyfish - Carabantes, Natalia; Cerqueda-García, Daniel; García-Maldonado, José Q.; Thomé, Patricia E. (Frontiers in Marine Science, 2022)
Cassiopea xamachana is a model system for studies in animal symbiosis with algal symbionts. This medusa is also associated with a microbial community that can impact its health, but this community has not been thoroughly studied. Shifts in the bacterial community following the loss of symbionts involving stress, environmental changes, or seasonal fluctuations can be complex, as the role of symbionts in structuring this community is not well established. To understand the interplay among microbial associates with this host, we explored the experimental diminishing of algal symbionts, and the influence of seasonal fluctuations over the structure of the bacterial community, through 16S rRNA gene high-throughput sequencing. Results showed that Gammaproteobacteria, Bacteroidia, and Alphaproteobacteria were dominant in all the mucus samples at the beginning of the experiments. However, after 28 days, bleached medusas showed a marked increase in Gammaproteobacteria, specifically in the genus Vibrio, as evidenced by Linear Discriminant Analysis of Effect Size (LEfSe). Seasons also resulted in shifts of the bacterial community, although bacterial genera were distinct from those found in bleached medusas, suggesting temporal associations with the host. According to PERMANOVA analysis, seasonal fluctuations affected the dominant bacterial members (p = 0.07), but symbiont presence was a more significant driver (p=0.001). We found the bacterial community of C. xamachana is like that of other jellyfish and corals, which furthers the interest in this animal as a study model. Defining relevant bacterial genera can help us understand the functional role of the holobiont members that assemble and maintain a healthy microbial community. Also, studies in other regions where C. xamachana distributes can help us define a core bacterial community for this medusa.